1996
DOI: 10.1109/79.543973
|View full text |Cite
|
Sign up to set email alerts
|

Genetic algorithms and their applications

Abstract: odeling is a common but important technique for signal characterization. With the advent of computational power, many problems that were considered to be unsolvable in the past can now be tackled with ease. Successful applications in this area include the time-delay estimation modeled as a finite impulse response (FIR) filter [ 11 for sonar and radar systems; speech coding using linear predictive coding [2-41; wavelets for speech and image coding and recognition [5-81; fractals for image compression and recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
302
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 816 publications
(306 citation statements)
references
References 26 publications
0
302
0
4
Order By: Relevance
“…Porto et al [21] used evolutionary programming to train neural networks to distinguish between sonar reflections from different types of objects: man-made metal spheres, seamounts, fish and plant life, and random background noise. Tang et al [22] survey the uses of genetic algorithms in acoustics and signal processing.…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…Porto et al [21] used evolutionary programming to train neural networks to distinguish between sonar reflections from different types of objects: man-made metal spheres, seamounts, fish and plant life, and random background noise. Tang et al [22] survey the uses of genetic algorithms in acoustics and signal processing.…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…Thus, the average objective value of the population is mapped into the average fitness [17]. After fitness values,…”
Section: Genetic Algorithm For Frame Selectionmentioning
confidence: 99%
“…Similarly to genetic algorithms [2], GSA is an optimization tool based on a population, where each member is seen as a mass, and each mass is a potential solution to the problem under analysis. It has already been shown that GSA is comparable in performance with other evolutionary algorithms such as particle swarm optimization (PSO) [3] and Genetic Algorithm (GA) [2].…”
Section: Introductionmentioning
confidence: 99%